(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This work is a comparative analysis of Russian and Uzbek proverbs and sayings in order to identify their similarities and differences in content, structure and functional purpose. Using the comparative method, the study is based on the analysis of the themes, form and structure of expressions, as well as their functional purpose in the context of cultural traditions and values. The results obtained allow for a deeper understanding of the unique features and common features of the Russian and Uzbek cultures, as well as their influence on the formation of the worldview and identity of each nation.